The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/scd.12068
|View full text |Cite
|
Sign up to set email alerts
|

Dental findings in children with West syndrome

Abstract: Patients with WS seem to have low caries experience, can have a deep palate, and may have their tongue positioned between the arches or on the incisive papilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…Case reports on West syndrome documented by Regis [10], Neta [11] and Khatri et al [12] showed similar intra oral findings i.e. multiple white spot lesions on labial surfaces, generalized tooth wear, altered chronology of teeth and gingival inflammation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Case reports on West syndrome documented by Regis [10], Neta [11] and Khatri et al [12] showed similar intra oral findings i.e. multiple white spot lesions on labial surfaces, generalized tooth wear, altered chronology of teeth and gingival inflammation.…”
Section: Discussionmentioning
confidence: 69%
“…Gingival enlargement is likely due to poor oral hygiene and white spot lesions are due to high sucrose diet and sugar containing medications. Neta [11] reported other oral findings like anterior open bite with tongue interposition in between arches, altered chronology, fissured tongue and low caries experience.…”
Section: Discussionmentioning
confidence: 98%
“…The dental treatment of patients with social development needs and impaired psychomotor presents challenges, such as impaired communication, severe intellectual deficit, inability to obey commands and follow oral hygiene instructions [3], difficulties in cooperation with the treatment, and fear of strangers [6].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of WS is 1 per 2000-4000 individuals born alive. It is more frequent in males; it is responsible for 2-10% of the causes of childhood epilepsies [2] and can be associated with other systemic conditions or syndromes [6]. WS occurs in children from all ethnic groups [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation